Rights of migrant workers under Malaysian employment law - Ab. Hamid, Zuraini; Abdul Shukor, Siti Fazilah; Ali Mohamed, Ashgar Ali (Yijun Institute of International Law, 2018)
Labour migration is an important global issue that largely affects the labour market. Malaysia is among the popular destination countries for labour migration in Asia. The number of migrant workers that consist of documented and undocumented workers is increasing every year due to rapid economic development that captivates job seekers from undeveloped countries. In this regard, migrant workers frequently fall into the trap of unscrupulous employers who exploit them for their own interests. These employers do not pay their wages as promised and deny them their employment rights. This case is basically treated as ‘forced labour’ or ‘human trafficking’ by the Malaysian authority. This paper identifies the Malaysia’s legal framework of the employment of migrant workers. In addition, how to address the infringed rights of migrant workers is discussed in this paper. Although the framework deems comprehensive, it further recommends a stringent and fair law enforcement to combat exploitation towards migrant workers.